Método montessori y su impacto en el área cognitiva de los niños del subnivel inicial 2 de la Escuela Aurora Estrada y Ayala de Ramírez Pérez, cantón Babahoyo - Bajaña Fajardo, Adriana Cecibel (2018)
The activities before the school stage, especially in the beginning, have seen the imperative need to fit into the lives of the children without altering their natures, which suggests that it is necessary to venture into the activities that help them naturally in the development of their abilities, the same ones that have been studied and expressed in the Montessori Method by the doctor of the same name, which devotes its actions of its first developments, these activities are usually related to the experiences in children's freedom and girls, with concrete materials in determining environments and integral curricula and with it, it draws on their knowledge and gives their first interrelations with the environment. The aim of this research is to demonstrate the influence of the Montessori Method in the cognitive area of children of the initial sub-level 2 of the Aurora Estrada and Ayala school of Ramírez Pérez, Babahoyo canton, for which it is necessary to determine the methodology, starting with the type of exploratory, descriptive and explanatory research applied in a systematic way according to the needs, the inductive and deductive methods, the techniques of information collection beginning with the observation, then with interview and surveys, whose instrument was the questionnaire of questions semi-structured, open and closed, formally and informally. On the other hand, it is concluded that there are few teachers that include activities of which the Montessori Method suggests, which limits the development of children's cognitive area, which hinders its application and obtaining positive results, for this reason it is presented the proposal to prepare a guide for the application of the Montessori Method in the teaching-learning process.